Complete response to induction therapy in patients with Myc‐positive and double‐hit non‐Hodgkin lymphoma is associated with prolonged progression‐free survival. Issue 11 (27th February 2014) - Cohen, Jonathon B.; Geyer, Susan M.; Lozanski, Gerard; Zhao, Weiqiang; Heerema, Nyla A.; Hall, Nathan C.; Nagar, Veena A.; Hemminger, Jessica A.; Jones, Jeffrey A.; Porcu, Pierluigi; Christian, Beth A.; Baiocchi, Robert A.; et al.
Abstract : BACKGROUND: Myc ‐positive B‐cell non‐Hodgkin lymphoma (NHL) with or without a B‐cell chronic lymphocytic leukemia/lymphoma 2 ( BCL2 ) rearrangement is associated with inferior progression‐free survival (PFS) and overall survival (OS). In this study, the authors reviewed the outcomes of patients with myc ‐positive and double‐hit NHL at The Ohio State University. METHODS: All patients who had non‐Burkitt, aggressive B‐cell NHL from 2008 to 2011 were assessed for the t(14;18) translocation and for v‐myc avian myelocytomatosis viral oncogene homolog ( CMYC ) rearrangements at diagnosis, and all myc ‐positive patients were included in the current analysis. Associations with clinical characteristics were described, and univariable and multivariable models were used to assess correlations between clinical variables and outcomes. RESULTS: Of 49 myc ‐positive patients, 29 patients also had BCL2 rearrangements (double‐hit NHL). No patients underwent autologous stem cell transplantation in first remission. For all myc ‐positive patients, the median PFS was 16.6 months, and the median OS was 37.7 months. For patients who had double‐hit NHL, the median PFS was 8 months, and the median OS was 12.5 months; whereas the median PFS and OS were not reached for myc ‐positive patients. A complete response (CR) after front‐line therapy, the presence of t(14;18), International Prognostic Index (IPI) group, and age were associated with PFS; whereas only the achievement of a CR and age >60 years were associated with OS in the multivariable setting. The median PFS was 3.3 months, and the median and OS was 7.0 months for patients who did not attain a CR; and the medians were not reached for patients who achieved a CR ( P < .00001). CONCLUSIONS: The achievement of a CR with front‐line therapy is associated with a prolonged PFS and OS in patients with myc ‐positive NHL, even after adjusting for type of initial therapy, histology, age, IPI, or the presence of a concurrent BCL2 translocation. Cancer 2014;120:1677–1685 . © 2014 American Cancer Society . Abstract : Patients with Myc‐positive or double‐hit non‐Hodgkin lymphoma have inferior progression‐free and overall survival. The authors identify a subset of patients who achieve a complete response to induction therapy who have prolonged remission durations.